PERSEPSI PENGUNJUNG TERHADAP KENYAMANAN BERAKTIVITAS TERKAIT KEBERADAAN PEDAGANG KAKI LIMA DI LAPANGAN MERDEKA MEDAN - Sitompul, Ria Angelida; Aritonang, Emmy Ria; Peranginangin, I (Unika Santo Thomas, 2019)
The purpose of this study was to find out the visitor's perception of the convenience of activities related to the presence of street vendors on Merdeka Square in Medan. The researcher collected data through the distribution of questionnaires consisting of three parts, namely in the first section containing Respondent Data, the second part contained eight Closed Questions, and in the third section contained four Open questions. This questionnaire was given to visitors to Merdeka Square as many as 45 respondents. The results of the Respondent's Answer are then tabulated, where each answer has an assessment weight. The first stage of processing the results of this assessment is to find the average analyzed based on Quartile on eight indicator variables, and test the validity of the questionnaire variables. Validity test is used to compare the correlation index r product moment Pearson with a significance level of 5%. which tells the assessment of all visitors to the presence of Street Vendors at Merdeka Square in Medan. The results of respondents' evaluations based on quartile analysis showed that the assessment score was at 958, which means that it was known that visitor perceptions of the presence of street vendors in Merdeka Square were quite negative. This is related to the convenience of Visitors in carrying out activities at Merdeka Square.